Ultrathin-Layer Structure of BiOI Microspheres Decorated on N-Doped Biochar With Efficient Photocatalytic Activity - Hou, Jianhua; Jiang, Ting; Wei, Rui; Idrees, Faryal; Bahnemann, Detlef (Frontiers in Chemistry, 2019)
Bismuth oxyiodide (BiOI) is among the most potential photocatalysts due to its photocatalytic activity under visible light irradiation. However, the photoinduced carrier separation efficiency has limited the BiOI photocatalytic activity. Herein, we utilized the direct carbonation of sapless cattail grass to obtain N-doped hierarchical structure cattail-based carbon (NCC). The NCC not only served as an appropriate host but also as a self-sacrificing template for BiOI microspheres for the preparation of BiOI/NCC composite material. The acidic solutions (HCl or AcOH) were used as a solvent which helped to obtain a well-defined micro/nano hierarchical BiOI microspheres composed of ultrathin nanosheets. Thus, BiOI/NCC composites were successfully designed through the in-situ self-template rapid dissolution-recrystallization mechanism. Additionally, numerous well-contacted interfaces were formed between NCC and BiOI, which served as an electron-acceptor bridge function for ultrafast electron transfer process in order to hinder the electron-hole pairs recombination. On account of the multiple synergistic effects of micro/nano hierarchical microsphere structure, ultrathin nanosheets and well-contacted interface, the as-prepared BiOI/NCC composites exhibit the superior degradation of rhodamine B (RhB) than pure BiOI under visible light irradiation.